Assessing aerobic endurance in swimming - Dekerle, J.; Pelayo, P. (World book of swimming: From science to performance, 2012)
Lactate threshold, Maximal Lactate Steady State (MLSS), and Critical Swimming Speed (CSS) represent distinct measures of endurance fitness. Each parameter can be used to assess a discrete aspect of swimming endurance. The lactate threshold can be identified from changes in the capillary blood lactate concentrations during an incremental step test. Alternative and non-invasive methods using open indirect calorimetry have recently been applied in swimming. Several 30-min sub-maximal constant speed tests need to be performed to determine MLSS, seen by some physiologists as the criterion measure of aerobic endurance. However, CSS is perceived in swimming as a more practical method for assessing aerobic endurance as it only requires the performance of several shorter maximal efforts to exhaustion. For coaching purposes, the 60-min and 30-min time trial tests could be effective for estimating MLSS and CSS. For any of these methods, both validity and reliability have to be established before being applied in research or practical settings. Given the narrow spectrum of submaximal speeds in swimming, good precision in the estimation of endurance speeds is a priority.